Percutaneous microwave ablation applications for liver tumors: recommendations for COVID-19 patients. Issue 3 (March 2021) - Afaghi, Pooya; Lapolla, Michael Anthony; Ghandi, Khashayar
Abstract: Microwave ablation (MWA) is an alternative locoregional therapy to surgical resection of solid tumors in the treatment of malignancies, and is widely used for hepatic tumors. It has a slightly higher overall survival (OS) rate compared to external beam radiation therapy (EBRT), and proton beam therapy (PBT), and better long-term recurrence-free OS rate compared to radiofrequency ablation (RFA). In this paper, current commercial devices, most recent noncommercial designs, and the principles behind them alongside the recently reported developments and issues of MWA are reviewed. The paper also provides microscopic insights on effects of microwave irradiation in the body. Our review shows that MWA is a safe and effective, minimally invasive method with high ablation completion rates. However, for large tumors, the completion rates slightly decrease, and recurrences increase. Thus, for large tumors we suggest using a cooled shaft antenna or multiple antenna placements. Comparisons of the two common ablation frequencies 915 MHz and 2.45 GHz have shown inconsistent results due to non-identical conditions. This review suggests that 915 MHz devices are more effective for ablating large tumors and the theory behind MWA effects corroborates this proposition. However, for small tumors or tumors adjacent to vital organs, 2.45 GHz is suggested due to its more localized ablation zone. Among the antenna designs, the double-slot antenna with a metallic choke seems to be more effective by localizing the radiation around the tip of the antenna, while also preventing backward radiation towards the skin. The review also pertains to the use of MWA in COVID-19 patients and risk factors associated with the disease. MWA should be considered for COVID-19 patients with hepatic tumors as a fast treatment with a short recovery time. As liver injury is also a risk due to COVID-19, it is recommended to apply liver function tests to monitor abnormal levels in alanine aminotransferase (ALT), aspartate aminotransferase (AST), total bilirubin, and other liver function indicators. Abstract : Microwave, ablation, percutaneous, liver, tumor, hepatocellular carcinoma, COVID-19